Economics of child labour - Fatima, Ambreen. (2013)
The dissertation aims to explore the supply and demand side determinant of child labour at macro, meso and micro level. At macro level it explores the effect of globalization (defined as openness to trade and inflow of foreign direct investment) and credit market imperfections on child labour. At meso level it explores the effect of labour market conditions on child labour. As the above two levels of analysis are mainly concerned with the demand for child labour, the micro level analysis explores the supply side determinant of child labour. At micro level this dissertation explores the effect of intrahousehold distribution of power on child related outcome. Specifically it explores the effect of mother’s decision making power on her child’s labour and schooling. The macro level analysis is based on cross country regression framework while meso and micro level analysis is based on the data from Pakistan.